Prototype Standarisasi HL7 SIMRS Rawat Jalan RSUD Kabupaten Kediri dengan RSUD Simpang Lima Gumul - Deni Luvi Jayanto; Eva Firdayanti Bisono; Sri Nurcahyati; Nadya Vira Mahmuna; Nadya Izzaty Maulana; Ervan Aditya Wirawan (Politeknik Negeri Jember, 2023)
Standardization in health data is a current need to help patients get the best service. Standard Health Level 7 (HL7) is an alternative in managing patient data, especially for health service data when patients visit hospitals, especially Kabupaten Kediri Hospital and Simpang Lima Gumul Hospital. HL7 is one of the standards that support the existence of telemedicine so that it can be implemented to optimize services. In addition, considerations in making designs such as color, layout and control are important aspects in making interfaces. The purpose of this research were to knew the data components, form of messages in HL7, and to design interfaces based on color, layout and controls. This study used a qualitative descriptive of observations on the registration of the Hospital Information System (SIMRS) and interviews with 6 officers. As a result, a comparison has been made between the HL7 data components and the two hospitals. Translation of the patient data form into the message form to HL7 has also been carried out. The evaluation of the interface design has been carried out for officers by prioritizing aspects of color, layout and control. It was concluded that the two hospitals met the standards for exchanging health data, but there was still data such as Px Group, Date Check, Register Hours, Sign in, Polychlinic 1, Information, Blood Group, Occupation, Father's Name, Husband/Wife's Name, Guarantor, PND and Email that needed attention.